Assessing and Modelling the Efficacy of Lemna paucicostata for the Phytoremediation of Petroleum Hydrocarbons in Crude Oil-Contaminated Wetlands - Abraham Ogheneruemu Ekperusi; Eunice O Nwachukwu; Francis D Sikoki (Scientific Reports, 2020)
The potentials of the invasive duckweed species, Lemna paucicostata to remove pollutants from aquatic environment was tested in a constructed wetlands as an ecological based system for the phytoremediation of petroleum hydrocarbons in crude oil-contaminated waters within 120 days. Total petroleum hydrocarbons in wetlands and tissues of duckweed were analyzed using gas chromatography with flame ionization detector following established methods while the experimental data were subjected to the first-order kinetic rate model to understand the remediation rate of duckweed in wetlands. L. paucicostata effected a significant (F = 253.405, P < 0.05) removal of hydrocarbons from wetlands reaching 97.91% after 120 days. Assessment on the transport and fate of hydrocarbons in duckweed indicated that L. paucicostata bioaccumulated less than 1% and significantly biodegraded 97.74% of hydrocarbons in wetlands at the end of the study. The experimental data reasonably fitted (r2 = 0.938) into the first-order kinetic rate model. From the result of the study, it is reasonable to infer that L. paucicostata is an effective aquatic macrophyte for the removal of petroleum hydrocarbons in moderately polluted waters.
Keywords: Phytoremediation; Duckweed; constructed wetlands; hydrocarbons; TPH